Suspicion of neglect or abuse in two hospitalized cases (Case report) - Moersintowarti B. Narendra; Hardjono Soeparto; Yustina Rosanti; Agus Salim (Paediatrica Indonesiana, 2001)
The convention of children’s rights (1989) has acknowledged and recommended a statement that minimalstandard for the child welfare with the range of primary right to keep an outstanding life for the children’s development to theirmaximum potential, protecting from disturbances e.g. neglect and physical abuse.But, it is difficult to classify cases whetherrelated to the problem of neglect or abuse, especially in developing countries where discrepancies in health services isremain exist.Objective : To present two cases which have been overlooked to the possibilities of abuse and neglect.Discription of the cases :Case 1. A malnourished 2 years old boy who was admitted with diarrhea in Dr.Soetomo HospitalSurabaya (September 6 ,1998) with :Clinical criteria of Marasmic Kwashiorkor available.Ignorance of health worker aboutnutritional status and inadequate referral system. 3. Factors related to the malnutrition are: a. Early weaning and inadequateweaning food. b. Poverty and low education. c. Lack of integrated health care (GOBI FFF practice). Case 2. An epileptic 11years old girl was admitted in Dr.Soetomo Hospital Surabaya (July,12, 1999). Problems list were : Respiratory problem whichcould not be explained pathophysiologically. Single parent, and inconsistency of adequate childrearing , Factors related to thefailure in compliance of epileptic treatment, and Isolation and restricted movement.Discussion of the difficulty in classificationof the cases, and the possibility of solving the problem in Surabaya related to the limited action of the Committee on ChildProtection, need to have positive suggestions sharing experience from the Congress members.